Succinic acid Production Strategy: Raw material, Organisms and Recent Applications in pharmaceutical and Food: Critical Review - Abd Alsaheb, Ramzi A.; A. Atiya, Mohammed; Kamil Abdullah , Jaafar; Abbas, Azza Hashim (Al-Khwarizmi Engineering Journal, 2023)
Succinic acid is an essential base ingredient for manufacturing various industrial chemicals. Succinic acid has been acknowledged as one of the most significant bio based building block chemicals. Rapid demand for succinic acid has been noticed in the last 10 years. The production methods and mechanisms developed. Hence, these techniques and operations need to be revised. Recently, an omnibus rule for developing succinic acid is to find renewable carbohydrate Feedstocks. The sustainability of the resource is crucial to disintegrate the massive use of petroleum based-production. Accordingly, systematically reviewing the latest findings of bacterial production and related fermentation methods is critical. Therefore, this paper aims to study the latest research and assess the findings statistically comprehensively. The current review attempt is a step toward comprehending all the conditions surrounding succinic acid production from raw materials, microorganisms, and fermentation methods.